Anatomical Characteristics and Variation Mechanisms on the Thick-Walled and Dwarfed Culm of Shidu Bamboo (Phyllostachys nidularia f. farcta) - Wang, Yujun; Qiao, Guirong; Xu, Jing; Jin, Kangming; Fan, Minyuan; Ding, Yulong; Wei, Qiang; Zhuo, Renying (Frontiers in Plant Science, 2022)
Wall thickness and internode length of bamboo culm are two important morphological indexes to bamboo utilization. However, little is known about their formation process and potential mechanisms. Phyllostachys nidularia f. farcta (Shidu bamboo) is a stable bamboo variant, which has thickened culm wall and shortened internode. Using anatomical, mathematical statistics, physiological detection as well as genomics methods, we systematically investigated the cytological essence and potential mechanism in the morphological variation of its culm. We discovered that the ground tissue largely transverse increasing in the inner layer of its culm wall, which is the mainly factor leading the wall thickening in the variant. Longitudinally, significant morphological changes occurred in both the fiber cells and parenchyma cells in the culm wall of Shidu bamboo. In addition, the main chemical components of the cell wall were significantly different between the variant and its prototype bamboo culm. A series of genes involved in gibberellin synthesis pathway and cell wall component synthesis is differentially expressed between Shidu and its prototype bamboo, which may be playing an important role in the process of internode elongation in bamboo plants. For the volume of individual internode in the culm of Shidu bamboo, the increase of wall thickness and the reduction of external size of internode only have a significantly impact on the internodes at the upper and lower part of its culm, which suggest that the significant decrease of the biomass of the culm of Shidu bamboo may be mainly related to the decrease of the total internodes number and the content of the main chemical components of its culm wall. The above results comprehensively explored the cytological essence and the biological mechanism underlying the morphological variation of culm in Shidu bamboo, and analyzed the principal factors leading to the decrease of its culm biomass.